Motivation from the Viewpoint of Expectation Theory: A Case Study in a Military Hospital (Research, Society and Development, 2020)
This research aimed to identify the profile and expectations of civil servants (civil and military) in the Administrative Division of a Military Hospital in Santa Maria, based on the Theory of Expectation. Such an approach is justified by the need to establish the relationship between the Theory of Expectation and its applicability, through a case study at the Military Health Organization, interviews were conducted with semi-structured questions. In general, it was evidenced: satisfaction with the profession; career changes that impacted expectations; the perception of the benefits offered by the institution; the alignment of the institutional mission with the work performed; recognition of work by managers, colleagues and the institution; the rewards and motivation for the work are directly related to expectations, difficulties, external and mission values; in order to lead the employees to a result that takes into account the rewards directed to their personal goals.